Did Covid-19 Pandemic Raised Tax Incomes in Bad Economic Situations? - Almino Situmorang; Said Kelana Asnawi; Etty Puji Lestari (Indonesian Journal of Business Analytics, 2024)
The fact that COVID-19 pandemic affected economic situation is known widely, but many companies actually can use ratios for measuring financial situation. If we look deeper, financial ratios can give actual fact about the financial performance periodically. The aim of this research is to find out whether liquidity ratios, Solvability ratios, activity ratios, profitability ratios, and tax ratios have an effect on financial performance. This research was conducted on companies listed on the Indonesia Stock Exchange in 2019 - 2023 with a sample of 117 companies for five years. Thus, the number of samples used in this research was 585. The independent variables in this research were liquidity ratios, Solvability ratios, activity ratios, profitability ratios, and tax ratios, while the dependent variable was financial performance. The data analysis method uses the difference test analyze method with SPSS version 26 software. The results of different tests for liquidity ratios show that there is no significant difference between the years before the COVID-19 pandemic, during the COVID-19 pandemic and after the COVID-19 pandemic. The results of different tests for the Solvability ratios, activity ratios, profitability ratios, and tax ratios showed that there was no significant difference between the years before the COVID-19 pandemic, during the COVID-19 pandemic and after the COVID-19 pandemic.